INTERNAL QUALITY ASSURANCE DEVELOPMENT AND EMPLOYABILITY: A Case Study of Private Higher Education in Cambodia - Chanthoun, Dr. Reth (jfpublisher, 2024)
Quality assurance has been a regulatory obligation in Cambodian colleges since 2003, yet it remains a relatively new idea. There is no official quality-management structure at the systemic level, and little attention has been devoted to this in the higher education sector. This study seeks to identify the internal quality elements that influence employability and quality improvement in higher education. The study uses a quantitative approach for measurement, with 200 accurate structured questionnaires sent to the public. Inferential statistics were used to do quantitative data analysis. Inferential statistics of data were presented using regression analysis and multiple regressions. This study found that leadership, academic staff, physical facilities, student evaluation, and teamwork all had a favorable impact on quality improvement. Mission approach and curriculum do not appear to have statistically meaningful effects on quality improvement. Furthermore, the study found a weak positive association between the quality of higher education and employability in higher education. The current study aims to investigate how internal quality improvement influences graduate employability and helps to the growth of private institutions in Phnom Penh, Cambodia.